Unbalanced cartilage calcification during development contributes to the formation of irregular articular surfaces as revealed by micro-CT images - Zhang Yuejiao; Zhang Jing; Xu Lingfeng; Wang Meiqing (Australasian Orthodontic Journal, 2023)
The histological features of irregular mandibular condylar surfaces revealed on CT images remain unknown.